PENGARUH GAYA HIDUP, LITERASI KEUANGAN, INTENSITAS PENGGUNAAN MOBILE PAYMENT TERHADAP SPENDING HABITS - Komang Trianingsih; Luh Putu Mahyuni (LPSDI Bina Patria, 2023)
The purpose of this study was to examine the impact of lifestyle and financial literacy on mobile payment usage intensity and spending habits. The population in this study is millennials using mobile payments in Indonesia. The number of samples in this study were 614 respondents. Data collection was conducted by distributing questionnaires to respondents. In this study, questionnaires were distributed online in the form of Google Sheets, using all types of social media. In this study, the analysis used was path analysis. The results show that lifestyle and financial knowledge have a significant positive impact on the intensity of mobile payment usage and spending habits. The intensity of mobile payment usage has a significant positive impact on spending habits. The study also found that lifestyle and financial literacy, as well as the intensity of millennials' use of mobile payments, indirectly influence spending habits. The conclusion of this study is that spending habits can be influenced by lifestyle, financial literacy, and the intensity of the use of mobile payments in the millennial generation in Indonesia.